The Psychopragmatics of Compliment Speech Acts in Teacher Student Classroom Interaction - Ramadona, Ance Ayu; Murtadho, Fathiaty; Anwar, Miftahulkhairah (FKIP - Universitas Riau, 2026)
This study examines the psychopragmatic aspects of compliment speech acts in teacher–student interactions among Grade VIII students at SMP Nizamia Andalusia, Jakarta. The research aims to identify the forms and functions of compliments and to analyze their perlocutionary effects within classroom communication. A qualitative descriptive approach was employed, with data collected through direct observation and analysis of naturally occurring utterances during classroom interactions from July to September 2025. The findings indicate four types of compliment speech acts: ability, personality, possession, and appearance, with ability-based compliments appearing most frequently. The dominant communicative function identified is positive evaluation, followed by expressions of solidarity, mild verbal teasing in humorous contexts, and expressions of admiration. From a psychopragmatic perspective, compliments serve not only as linguistic evaluations but also as psychological reinforcement that fosters positive emotions and interpersonal harmony. The perlocutionary effects include increased self-confidence, stronger learning motivation, and the development of social values such as empathy and cooperation. This study contributes to psychopragmatic scholarship and offers practical implications for teachers in developing effective and supportive classroom communication strategies.